The Relationship of Motivation and Workload with the Performance of Health Officers in the Work Area of Puskemas Pedongga Pasangkayu District - Serly; Sudirman; Zhanaz Tasya (Yayasan Sinergi Kawula Muda, 2024)
Performance in every organization is carried out by human resources available in an organization. In an organization at the Puskesmas, the performance or work results in quality and quantity can be achieved by a health worker if he carries out his main duties and functions as an employee in accordance with the responsibilities assigned or given to him. The purpose of this study was to determine the relationship between motivation and workload with the performance of health workers in the Pedongga Health Center Work Area, Pasangkayu Regency. This type of research is an analytic type of research using a Cross Sectional Study approach where data concerning the data of the independent variable and the dependent variable will be collected at the same time. The number of samples in this study were 37 health workers who work in the Pedongga Health Center Work Area, Pasangkayu Regency (total population). The results showed that there was a significant relationship between workload with p value = 0.033 (p < 0.05), and motivation with p value = 0.005 (p < 0.05) with the performance of health workers in the Pedongga Health Center Work Area, Pasangkayu Regency. The conclusion in this research is that all the independent variables studied have a relationship with the dependent variable, which means that workload and motivation have a relationship with the performance of health workers. Suggestions in the study are expected for the related agencies of the Pedongga Public Health Center, Pasangkayu Regency to be able to improve the performance of health workers so that public health services at the Puskesmas are better.